Mobiliser ses réseaux pour défendre son honneur : une stratégie pour obtenir justice des maréchaux de France aux xviie et xviiie siècles - Romain Benoit-Lévy (Criminocorpus)
This article analyzes the times and forms of mobilization of different types of networks in honor cases brought before the Tribunal des maréchaux de France. This sovereign royal court has had the mission, since the middle of the 16th century, to offer a judicial, non-violent and honorable issue for the point d’honneur of nobles and soldiers. Entrusted to the maréchaux de France, it is there to prevent duels. In this specific context, the mobilization of parents, friends, allies, protectors or servants takes place at specific times during the procedure. But this strategy of mobilizing third parties is a double-edged sword and can backfire on the litigant. All the more so since, in the context of arbitration proceedings, the networks that can be mobilized by litigants are also mobilized by the judges themselves. Even when they are isolated and without any relational capital, litigants never find themselves alone before the judges of the point d’honneur.